المنظومة الأخلاقية في الإسلام وأثرها في تحقيق الأمن الفكري - علي، على أبو بكر إبراهيم (جامعة الأزهر - كلية اصول الدين والدعوة الإسلامية بطنطا, 2019)
يهدف هذا البحث إلى بيان دور الأخلاق الإسلامية في تحقيق الأمن الفكري، ويبين كيف أن الأخلاق في الإسلام هي أحد أهم ركائز الأمن المجتمعي، ولذلك حاولت أن أجيب عن تلك الأسئلة، ما هي منظومة الأخلاق في الإسلام؟ وما هي خصائصها؟ وما هي فوائدها التي يمكن أن تحقق أمنا فكريا للمجتمع المعاصر. ثم بحثت كيف أن الأخلاق في الإسلام تتصف بالثبات، ولا تتغير حسب الأهواء والمصالح الشخصية والمنافع الفردية، ثم درست الأخلاق النفسية؛ خاصة الحياء والعفة وبينا دورهما في تحقيق الأمن الفكري. أما الأخلاق العملية مثل العدل والحكمة والصبر، فقد أثبتنا في بحثنا هذا، كيف أن هذه الأخلاق تعد محاور رئيسية في تحقيق الأمن الفكري. وخلق الحكمة هو رادع لأي تهور وطيش يصدر في المجتمع، وكذلك خلق الصبر هو وسيلة عظيمة في تحقيق الأمن الفكري والاجتماعي، حيث إن خلق الصبر يحل المشكلات بين الناس، وبالصبر تتمكن الأمة من تجاوز المحن التي تواجهها، وتحقق الأمة كل ما تريد من أهداف بالصبر. وكانت أهم النتائج التي توصلت إليها هي أن منظومة الأخلاق في الإسلام تتصف بالكمال والشمول، كما تعمل على تحرر الإنسان من الغضب والشهوة والظلم، وذلك يسهم بلا شك في تحقيق الأمن الفكري. كما يوصي الباحث بأن تكون هناك بحوثا مستقلة تخص كل نوع من أنواع الأخلاق، فخلق العدل يستوجب بحثا مستقلا لكي يبرز أثر هذا الخلق في تحقيق الأمن عموما والأمن الفكري خصوصا.
This research aims to explain the role of Islamic ethics in achieving intellectual security, and shows how ethics in Islam is one of the most important pillars of community security. We try to answer these questions: what is the system of ethics in Islam, and what are their characteristics? What are the benefits of ethics in Islam and how it can bring intellectual security to the modern society؟ We examine how morality in Islam is characterized by stability, and does not change according to whims, personal interests and individual benefits. We also study psychological ethics; especially modesty and chastity and show their role in achieving intellectual security. The researchers demonstrate also how practical ethics, such as justice, wisdom, and patience, are key themes in achieving intellectual security. The ethic of wisdom for example is a deterrent to any recklessness in the society. As for the ethic of patience, it is a great factor to achieve intellectual and social security, as it solves problems between people and by patience, the nation can overcome the adversity it faces and achieve all its goals. Finally, the researchers have many conclusions, the most important of which is that the system of morality in Islam is perfect and comprehensive, and works to free man from anger, lust, and injustice, and this undoubtedly contributes to the achievement of intellectual security. The researchers also recommend preparing an independent research on each type of ethics. Justice, for instance, requires an independent research in order to highlight its impact in achieving security in general and intellectual security in particular.
Keywords: الأخلاق الإسلامية -- الأمن الفكري -- الثقافة الإسلامية